Urinary Neopterin in Patients with Diabetes Mellitus and Foot Ulcers - Melicharova Karolina (Pteridines, 2007)
Increased urinary or serum concentrations of neopterin have been reported in disorders associated with systemic immune activation, e.g. viral infections, cancer, or autoimmune diseases, but the data on neopterin concentrations in patients with diabetes mellitus are limited. The aim of the present study was to investigate urinary neopterin concentrations in patients with diabetes mellitus and with or without diabetic foot. Urinary neopterin was determined by high-performance liquid chromatography in 51 patients with diabetes mellitus, including 19 patients with diabetic foot, and 18 healthy controls. Neopterin concentrations were significantly increased in patients with diabetes mellitus compared to controls (mean ± standard deviation; 221 ± 149 vs. 139 ± 66 μmol/mol creatinine; Mann-Whitney U test, p = 0.003). Urinary neopterin concentrations in patients with or without diabetic foot were identical (224 ± 113 vs. 219 ± 169 μmol/mol creatinine). No significant difference was also observed between patients with type 1 and type 2 diabetes mellitus, between patients treated with insulin compared to patients not treated with insulin, patients with or without diabetic retinopathy, with or without diabetic neuropathy, with or without diabetic nephropathy, with or without ischemic heart disease, with or without ischemic disease of lower extremities, and with or without ischemic cerebrovascular disease. Atrend of higher neopterin concentrations was observed in patients with any complication of diabetes compared to no complications (234 ± 164 vs. 176 ± 73 μmol/mol creatinine), and compared to controls, urinary neopterin was significantly increased only in patients with complications. No significant correlation was observed between urinary neopterin and glycosylated hemoglobin (rs = - 0.14, p = 0.39) or the duration of diabetes (rs = 0.25, p = 0.09). In conclusion, present results demonstrate that urinary neopterin is increased in patients with diabetes mellitus. No differences were observed in urinary neopterin concentrations based on type of diabetes, therapy or presence of diabetic foot, and urinary neopterin did not correlate with the glycosylated hemoglobin levels or duration of diabetes. Increased urinary neopterin concentrations in patients with diabetes mellitus is associated with the presence of complications and may reflect systemic immune activation associated with atherosclerosis.